Possible Interrelationship of Inflammatory Cells in Dry Type Cutaneous leishmaniasis - Elham Taheri; Shahriar dabiri; Manzoomeh Shamsi Meymandi; Ebrahim Saedi (Iranian Society of Pathology, 2017)
Background & Objective: There is a complicated interaction between leishmaniasis and the host immune cells, and also between the host immune cells. These interactions have fundamental effects on the outcome of the disease. The current study aimed at characterizing the number, distribution, co-localization, and interrelation of 4 types of inflammatory cells in different clinical forms of dry-type cutaneous leishmaniasis (CL). Methods: Thirty-nine cases of CL were studied. The cases were classified clinically as 14 cases of acute leishmaniasis with indurated papules, nodules, and plaques with central crust formation < 2 years, 7 cases of chronic type with non-healing lesions > 2 years, and 12 cases of lupoid leishmaniasis with characteristic papules around previous scars of CL > 2 years. Paraffin-embedded blocks were stained with hematoxylin and eosin (H&E) and also stained immunohistochemically for CD4, CD8, CD68, and CD1a. Results: In acute CL, there was a significant correlation between CD68+ macrophages and CD1a+ epidermal dendritic cells (DCs); the population of CD68+ macrophages and CD1a+ epidermal DCs increased in parallel. In lupoid CL, there was a significant correlation between CD1a+ epidermal DCs, and CD1a+ dermal DCs and population of CD1a+ epidermal DCs; the number of CD1a+ dermal DCs increased in parallel. Conclusions: The result of the current study could be used as a baseline to design and study the new targeted therapy of synergistic effects of macrophages and DCs to phagocytizing leishmania bodies; and/or suggestion planning of individualizing setup of vaccine by autologous interaction of macrophages and DC in CL.